Revealing the working principle of sodium trimetaphosphate as state of the art anti-creep agent in gypsum plaster - Schug, Benedikt; Mandel, Karl; Schottner, Gerhard; Shmeliov, Aleksey; Nicolosi, Valeria; Baese, Rauno; Foerthner, Sebastian; Pietschmann, Bernd; Biebl, Markus; Sextl, Gerhard (Cement and Concrete Research, 2018)
Sodium trimetaphosphate (STMP) is a state of the art anti-creep agent for gypsum plasterboards. It counteracts the deformation of gypsum in a humid environment under load. Despite the fact that STMP is the industrial standard as anti-creep agent, its working mechanisms is not yet thoroughly understood or published. In this work, the role of sodium trimetaphosphate as anti-creep agent of gypsum is reviewed with fundamentally new approaches and modern analytical methods. The surface interaction of trimetaphosphate with calcium sulfate dihydrate crystals is studied in dependence of different crystallographic facets. Via this approach, it was ultimately possible to reveal the working principle of STMP as a highly effective anti-creep agent and deduce a general understanding for anti-creep agents. These insights could help to find and judge new substances in light of their working principle as anti-creep agents.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Anti-creep agent; Gypsum plaster; Sag; Sodium trimetaphosphate